HAJI ABDUL KARIM AMRULLAH ULAMA PEMBAHARU ISLAM DI MINANGKABAU - Novita Siswayanti (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
Haji Abdul Karim Amrullah is an Islamic reformer from Minangkabau who played a significant role in dawah and tabligh in the spirit of purifying the practice of Islamic values from the practice of bid’ah, taqlîd, and khurafat. His struggle was in line with the philosophy of traditional Minangkabau ‘adat basandi syara’, syara’ basandi kitabullah’. Haji Abdul Karim Amrullah who was known as Haji Rasul preached Islamic teaching both in oral and in writing. Along with Kaum Mudo Minangkabau (the youth of Minangkabau), he shared his thoughts through the Al-Munir magazine. He enforced the foundation of Islamic reformation through education by establishing Surau Jembatan Besi (Madrasah Sumatra Thawalib) and Muhammadiyah as social foundations that concern about the nation. This study examines the figure and the role of Haji Rasul in the development and renewal of Islam in Minangkabau. By employing qualitative method, particularly the historical approach, this study investigates all aspects of Haji Rasul’s life. With this perspective, the profile of Haji Rasul is intensively revealed, ranging from his family background, social background, education, patterns of thought, religious works, dawah activities, his role in education, his institutions, and his impact to the society.